2021
DOI: 10.1101/2021.08.01.454634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial transformation of traditional fermented fertilizer bokashi alters chemical composition and improves plant growth

Abstract: Bokashi is an organic soil amendment that makes use of microbial processes to break down agricultural waste and create a nutrient-rich fertilizer. The benefits of various types of bokashi on soil fertility and plant growth are well documented, however the changes in microbial community composition and nutrients during bokashi maturation remain poorly characterized. Here, we aimed to identify potential differences in the quality of bokashi made using different ingredients and to investigate the biochemical tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…It has been observed that bokashi compost which was produced by using different organic wastes increases the chlorophyll levels and dry biomass values of cucumber (Cucumis sativus) and cabbage (Brassica napus subsp. pabularia) seedlings (Abo-Sido, Goss, Griffith, and Klepac-Ceraj, 2021). In an incubation study with bokashi compost was added to organic waste, chemical properties of the soil, nitrogen concentration and nitrogen mineralization were increased in the soil (Augusto, Luiz, and Beatriz, 2018).…”
Section: Bokashi Compostmentioning
confidence: 99%
“…It has been observed that bokashi compost which was produced by using different organic wastes increases the chlorophyll levels and dry biomass values of cucumber (Cucumis sativus) and cabbage (Brassica napus subsp. pabularia) seedlings (Abo-Sido, Goss, Griffith, and Klepac-Ceraj, 2021). In an incubation study with bokashi compost was added to organic waste, chemical properties of the soil, nitrogen concentration and nitrogen mineralization were increased in the soil (Augusto, Luiz, and Beatriz, 2018).…”
Section: Bokashi Compostmentioning
confidence: 99%
“…Studies evaluating chemical and organic acid changes throughout the fermentation process are rare (Yamada and Xu 2001;Abo-Sido et al 2021). A better understanding of fermentation processes can facilitate compost production and the combination of raw materials.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Bokashi promotes productive increment and causes benefits in the production system, increasing organic matter, fertility, and microorganisms (Khaeruni et al, 2020;Lasmini et al, 2018;Viana et al, 2020). Besides, many agriculture residues can be used as raw materials, which allows producers to produce from available materials (Abo-Sido et al, 2021).…”
mentioning
confidence: 99%